Spillover effect of FSS accounting inspection on audit hours of peer companies. Issue 3 (3rd May 2020) - Kim, Jeehong; Kim, Sooin; Cho, Eunjung
ABSTRACT: Financial misstatements detected by the Financial Supervisory Service (FSS)'s accounting inspection incorporate the possibility of erroneous accounting practice over the industry and the increasing scrutiny of supervisory institution. We investigate the spillover effect of financial misstatements detected by the FSS on audit efforts for peer companies. We find that auditors put longer hours in auditing peer companies and that audit hours for peers increase as auditors of misstating companies receive stronger sanctions. In addition, the increase of audit effort is more pronounced for the auditors who audited misstating company-years, Big4 auditors and for companies listed in more scrutinized market. Our results are robust after controlling for the firm-specific risk of having material accounting misstatements. As a result, this paper contributes to the related literature by confirming the increase of auditors' scrutiny after misstatement detection by the FSS and effectiveness of supervisory accounting inspections on a sampling basis.